0594 Predictors of Insomnia Severity Index Profiles Among Veterans with Obstructive Sleep Apnea. (27th April 2018) - Wallace, D M; Wohgemuth, W K
Abstract: Introduction: The Insomnia Severity Index (ISI) is an instrument assessing insomnia complaints and its associated daytime symptoms. It can identify insomnia in individuals with obstructive sleep apnea (OSA). However, whether different ISI profiles exist in individuals with OSA is unknown. This study aimed to identify 1) classes of ISI profiles and 2) predictors of class membership among veterans with OSA. Methods: Participants were 630 veterans with OSA diagnosed at the Miami VA Sleep Clinic. Veterans completed the ISI on the polysomnography night. Latent profile analysis (LPA) was used to determine ISI subgroups based on its 7 individual items. Then, the following covariates were examined to predict subgroup membership: age, apnea-hypopnea index (AHI), Charlson comorbidity index (CCI), mood disorder, post-traumatic stress disorder (PTSD), and chronic pain diagnoses. Results: Four ISI subgroups were identified. Groups 1, 2, and 3 had low, moderate, and high scores across all items with mean ISI scores of 6.9 (13% of sample, "No insomnia"), 15.8 (27% of sample, "Moderate insomnia"), and 22.6 (51% of sample, "Severe insomnia"), respectively. Group 4 was characterized by low scores on insomnia complaints but elevated scores on daytime symptoms with mean score of 14.6 (9% of sample, "Daytime symptoms only"). Relative to the "Severe" group, veterans were more likely to be in the "No insomnia" group if they were older and did not have 1) mood disorder, 2) PTSD, and 3) chronic pain. Similarly, veterans were more likely to be in the "Moderate" group if they were older and did not have 1) mood disorder and 2) chronic pain. The covariate that distinguished participants in the "Daytime symptoms" from the "Severe" group was the absence of mood disorder. The AHI and CCI were not related to any ISI subgroup. Conclusion: Psychiatric diagnoses, but not OSA severity or medical diagnoses, were related to more severe insomnia in veterans with OSA. Caution should be used when interpreting the ISI in individuals with OSA since a subset had elevated scores, but no insomnia. Support (If Any): None.